Outlaw : the Story of Robin Hood - Morpurgo, Michael (London: HarperCollins Children's Books, 2012)
Lost in a dark, strange forest, Robin is rescued by a crew of misfits. He yearns to seek justice against his cruel oppressors, to finally defeat the Sheriff of Nottingham, once and for all. After a fierce storm, a boy of today discovers a human skull, buried beneath the roots of an ancient tree. A skull with a legendary past: the heroic story of Robin Hood
Keywords: Children's stories